The effect of heat treatment on compression strength of recycled AA6061 aluminium chips - Mustapa, Mohammad Sukri; Abdul Latif, Noradila; Mohd Joharudin, Nurul Farahin; Mahzan, Shahruddin; Masirin, Mohd Idrus; Abdul Hamid, Norashikin (Trans Tech Publications, 2018)
Solid state recycling aluminium AA6061 chips by cold compaction is a technique that used lower energy consumption and operating cost compared to the conventional recycling technique by casting. This research is to investigate physical characteristics of the milled recycling aluminium AA6061 according to the change of the time (heat treatment) using the high speed milling process and followed by a cold press forging process. Physical property of the recycled aluminium chip of AA6061 were studied. On the other hand, the results were showing that the porosity and density, and compression is correlated. At 8 hours on variable of quenching have a best value porosity (1.95%), density (2.55 g/cm3 ) and compression strength (315.19 MPa). While for the variable of aging, the best value of density (2.54 g/cm3 ) and compression strength (280.76 MPa) is at 10 hours. On porosity the best value is at 8 hours (2.79 %). It must be considered to the density and compression strength. For that, 10 hours were chosen for the best aging time. It can be concluded; the best quenching time is 8 hours and aging time is 10 hours.